Synergistic operation between battery energy storage and photovoltaic generator systems to assist management of microgrids - Curi Busarello, Tiago Davi; Paredes, Helmo K. M. [UNESP]; Pomilio, Jose A.; Simoes, Marcelo G. (Inst Engineering Technology-iet, 2018)
This study presents a synergistic operation between a battery energy storage (BES) and a photovoltaic generator (PVG) system to assist management of microgrids. The BES and the PVG work synergistically in a virtual single agent. The single agent consists of a group containing the BES, the PVG, and the loads in a feeder. The single agent results in a virtual distributed energy resource, capable to obey orders imposed by the supervisory controller (SC). The loads within the single agent seem not existent anymore to the SC, but they kept fed all the time. This is convenient to the microgrid in terms of management because the SC interacts with only one element and not more with all elements within the single agent. The synergistic operation arises when the SC demands orders to the single agent. To make the single agent obey the SC, the BES and PVG need to decide their operation mode, working synergistically for each other. The conservative power theory is applied to quantify active power, reactive energy, and harmonic currents in points of interest along the microgrid. The efficacy of the synergistic operation is verified through experimental results.
Keywords: battery storage plants; photovoltaic power systems; distributed power generation; power system management; power system harmonics; battery energy storage; photovoltaic generator system; microgrid management; BES; PVG system; virtual distributed energy resource; supervisory controller; SC; conservative power theory; reactive energy; harmonic current